Plan de negocio para el montaje de una empresa procesadora y comercializadora de productos hortofrutícolas en Santiago de Cali (2011)
This research is developed with the goal of create the enough tools for the building of the enterprise NATURAL SAS, which will be dedicated to the agro-industrial elaboration of fruit pulp, fruit juice, fruits and vegetables extracts and fruit flour; these will be trade in “ la sultana del Valle”. Will apply as life project of the author and will pretend to contribute with the health, the employment, business sustainability, and the environment of the city. This business plan have as specific objectives to analyze the different aspects related with its develop such as: Environment, market, technical, administrative, legal, economic and financial analysis. This plan is focused to the food market, and is marked in a special regime in which rules health norms and the preservation of the human beings’ health trough innocuous products. The strategic planning will play an important role in the creation of the business’ idea, given the nature of the competitors, the natural dynamism of the sector and the possible lack of liquidity from the trade habits. Taking into account all these aspects and supporting in management and quality theories; was established a set of resources that allows to the project be commercially, technical, administrative, economic and financial able.